Awareness of Retinopathy of Prematurity (ROP) amongst Pediatricians in Pakistan - Agha Shabbir Ali, M. Moin, Nasira Inayat, Umar K. Mian, Ayesha Khalid (Pakistan Journal of Ophthalmology, 2016)
Purpose: To find the awareness of ROP among Neonatologists in Pakistan. Study Design: Quantitative and qualitative survey. Place and Duration of Study: National pediatric conference held at Lahore in March 2014. Material and Methods: A questionnaire was given to all the pediatricians and neonatologists at a national pediatric conference held at Lahore in March 2014. The answering pediatricians/neonatologists were divided into two groups. Group I consisted of 28 pediatricians who had worked for less than 5 years, and in group II, there were 34 pediatricians who had worked for more than 5 years. This questionnaire was especially constructed to assess knowledge, attitude, and practice (KAP) of Retinopathy among participants attending the conference. Results: A total number of 62 pediatricians/neonatologists participated in the study Majority of the 58pediatricians (93%) had heard about retinopathy of prematurity and 43 (69.4%) agreed that the infants must be checked for ROP. A few participants 15 (24%) stated that there is a ROP screening criteria, 44 (71%) responded negatively and 3 (4.8%) responded that there may be a criteria present. Forty eight (77.4%) stated that they did not have an ophthalmologist for ROP screening while 11 (17%) had an ophthalmologist. Thirty five (56.5%) agreed that there are treatment options for ROP but 20 (32.3%) were not sure about such treatment options. Thirty two (51%) agreed that a patient should be given reappointment within 3 days once he missed one. ROP was an important issue for 40 (64%) of doctors while 16 (25%) were not sure about this. There was insignificant difference with respect to years of experience as pediatrician and the questions asked. Conclusion: ROP awareness should be raised at a national level to improve the development of ROP screening and treatment services in Pakistan. Keywords: Retinopathy of Prematurity, Awareness, Screening, Neonatologist.